Firing of neuron pairs in the hippocampo-septal axis of the rat: cell types and their interactions during theta and non-theta states - Zaide, Josef (My University, 1980)
The behavioral and neuronal functions of the hippocampus, a major component of the brain's limbic cortex, are not well understood. One major clue to its role in behavior is that its gross electrical activity (EEG) shows striking correlations with behaviour. Special significance has been attached to the hippocampal theta rhythm, but, despite extensive research concerning the precise dimensions of behavior correlated with theta, it is still not clear if the presence of theta indicates that the hippocampus is actively involved in the control of behavior. In an attempt to describe some of the neuronal interactions that occur during theta, the activity of pairs of neurons in the hippocampus and septum was recorded in rats paralyzed with succinylcholine chloride.
In Section One it was seen that hippocampal EEG in paralyzed rats was not substantially different from the normal. Long trains of clear theta as well as irregular EEG were seen in the immobilized rat. In Section Two cells in hippocampo-septal sites were categorized. One of the neurons of the pair was usually in dorsal CA1; the other was located in the lateral septum (LSN) in a region shown to receive the terminals of the hippocampal projection cell (P cell). Typical cell types were seen in CA1: rhythmically bursting "theta" cells (B cells) and complex-spike cells. The A cell was probably the CA1 projection cell (pyramidal cell). Cells in the LSN (C cells) were characterized by a lack of bursting. The majority were slowly firing cells. In Section Three the activity of different cell types during different EEG rhythms was described. Firing patterns of A and B cells were similar to those described in other work: A cells tended to decline in rate during theta, while B cells increased in rate providing an initial indication that during theta hippocampal transimission to target zones is attenuated. The C cells did not generally show substantial changes in activity during EEG changes, although in some C cells a weak theta rhythm was detected.
In the last section (Section Four) an attempt was made to detect correlations between hippocampal and septal spike trains which could be indicative of a transsynaptic influence of P cells and to determine if such correlations changed as a function of EEG state. The cross-correlation of "naturally" occurring firing is not a standard tool in the analysis of complex mammalian forebrain circuits and so, this study was also an exploration of whether such an approach was practical in the analysis of complex circuits.
In the cross-correlograms of an appreciable number of cell pairs it was possible to detect changes in target cell firing which appeared to be due to a direct influence of P cell populations. Most of these changes consisted of increases in rates of septal neurons; for a smaller number of pairs, the occurrence of a hippocampal event was associated with a decrease in target cell firing. Most changes in septal cell firing occured during irregular EEG patterns. During theta, the firing of P cells was relatively ineffective in biasing the state of the septal cell. These results were interpreted in terms of a possible tendency for a greater number of P cells to fire more synchronously during irregular EEG. It was also found, in agreement with other studies, that the activity of P cells was relatively suppressed during theta, again suggesting that theta represents a state of attenuated output.
On the basis of the present findings, it can be tentatively conclude that, during theta, it is unlikely that the hippocampus is actively involved in behavioral expression; it is more likely that hippocampal output function is exerted during irregular EEG and associated behaviors, during which time it acts partially to excite septal cells.
Keywords: Psychology; Psychology